2019
DOI: 10.1002/ese3.354
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of emulsion and its field application for enhanced oil recovery

Abstract: Emulsification plays an important role in enhancing oil recovery. Experiments and field applications of alkali/surfactant/polymer (ASP) flooding indicated that the amount of oil recovery in liquids with emulsions is 5% higher than that in liquids with no emulsions. Therefore, it is of great significance to study emulsion and its field application for enhanced oil recovery. This paper discusses the current status of emulsion for enhanced oil recovery, including the formation mechanism of emulsions in chemical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 99 publications
0
73
0
1
Order By: Relevance
“…Interesting accounts of the current knowledge on emulsion flows for EOR can be found in the following recent review papers: refs. (Perazzo et al, 2018;Zhou et al, 2019) while a review on spontaneous emulsification in the context of EOR can be found in ref. (Li et al, 2020) The pore scale dynamics of emulsion flows in porous media are particularly complex since they feature both liquid-liquid interface instabilities that are characteristic of immiscible two-phase flow, and a non-Newtonian rheology.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting accounts of the current knowledge on emulsion flows for EOR can be found in the following recent review papers: refs. (Perazzo et al, 2018;Zhou et al, 2019) while a review on spontaneous emulsification in the context of EOR can be found in ref. (Li et al, 2020) The pore scale dynamics of emulsion flows in porous media are particularly complex since they feature both liquid-liquid interface instabilities that are characteristic of immiscible two-phase flow, and a non-Newtonian rheology.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the dispersed and continuous phase, emulsions are primarily categorized into oil in water and water in oil wherein water forms the continuous and dispersed phase respectively (Schramm 2014). Emulsions are widely applicable in a plethora of industries, including food (Shao et al 2020), membranes (Ahmad et al 2019), drug delivery (Yan et al 2019), cosmetic (Venkataramani et al 2020), personal care (Marto et al 2018), pharmaceutical (Kiss et al 2011), energy storage (Zhang et al 2019), and oil and gas (Zhou et al 2019), and their stability is of high significance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, conventional W/O and O/W emulsions are easy to prepare, with a lower requirement of emulsifier (surfactant) and no need for co‐surfactants. Generally, conventional W/O and O/W emulsions show great potential in a wide range of applications, such as in the food industry, encapsulation and delivery systems for nutrition, etc …”
Section: Introductionmentioning
confidence: 99%